2015
DOI: 10.1017/jfm.2015.360
|View full text |Cite
|
Sign up to set email alerts
|

Effects of inertia and viscoelasticity on sedimenting anisotropic particles

Abstract: An axisymmetric particle sedimenting in an otherwise quiescent Newtonian fluid, in the Stokes regime, retains its initial orientation. For the special case of a spheroidal geometry, we examine analytically the effects of weak inertia and viscoelasticity in driving the particle towards an eventual steady orientation independent of initial conditions. The generalized reciprocal theorem, together with a novel vector spheroidal harmonics formalism, is used to find closed-form analytical expressions for the O(Re) i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
137
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 63 publications
(145 citation statements)
references
References 92 publications
6
137
1
Order By: Relevance
“…That this approximation leads to a convergent integral may be seen by noting that, for a linear flow at Re = 0, we have u (1) s ∼ O(1/r 2 ) for r L, and from (2.11), it is then seen that (Du (1) s )/Dt ∼ O(1/r 2 ) for large r. Since u (2) ∼ O(1/r 2 ) for r L, the O(Re) integrand based on the Stokes approximation is O(1/r 4 ) for r L, implying convergence. As for the case of sedimentation in a quiescent fluid (Dabade et al 2015), this points to the regular nature of the O(Re) correction, with the dominant contribution to the O(Re) torque arising due to fluid inertial forces acting within a volume of order the size of the particle itself. It may be shown that the next correction to the angular velocity is O(Re 3/2 ), and is singular in character, arising from the effects of inertia acting on length scales of O(Re −1/2 ).…”
Section: Formulation For the Inertial Drift: The Generalized Reciprocmentioning
confidence: 95%
See 4 more Smart Citations
“…That this approximation leads to a convergent integral may be seen by noting that, for a linear flow at Re = 0, we have u (1) s ∼ O(1/r 2 ) for r L, and from (2.11), it is then seen that (Du (1) s )/Dt ∼ O(1/r 2 ) for large r. Since u (2) ∼ O(1/r 2 ) for r L, the O(Re) integrand based on the Stokes approximation is O(1/r 4 ) for r L, implying convergence. As for the case of sedimentation in a quiescent fluid (Dabade et al 2015), this points to the regular nature of the O(Re) correction, with the dominant contribution to the O(Re) torque arising due to fluid inertial forces acting within a volume of order the size of the particle itself. It may be shown that the next correction to the angular velocity is O(Re 3/2 ), and is singular in character, arising from the effects of inertia acting on length scales of O(Re −1/2 ).…”
Section: Formulation For the Inertial Drift: The Generalized Reciprocmentioning
confidence: 95%
“…Since the structure of the formalism, and a comparison with a similar expansion of the velocity field in terms of spherical harmonics, originally given by Lamb (for instance, see Kim & Karrila (1991, chap. 4)), has already been explained in some detail in Dabade et al (2015), we will be brief here. The formalism is based on expressing the general solution of the Stokes equations, around an arbitrary number of spheroidal particles, as a superposition of growing and decaying vector harmonics in local spheroidal coordinates defined with respect to a Cartesian system centred at each particle, and aligned with the particle axis of symmetry.…”
Section: The Solutions Of the Stokes Equations In Spheroidal Coordinatesmentioning
confidence: 99%
See 3 more Smart Citations